2017
DOI: 10.15376/biores.12.3.5279-5295
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Microscopic Changes of Paulownia Wood under Thermal Compression

Abstract: This study evaluates the microscopic changes of paulownia solid wood panels subjected to thermal compression via characterizing the changes in wood microstructure. The panels, with dimensions of 500 mm × 100 mm × 20 mm, were hot-pressed in a tangential direction by using a laboratorytype hot press at a temperature of either 150 °C or 170 °C and a pressure of 2 MPa for 45 min. Microscopic investigations conducted by light microscopy showed that slightly more damage occurred in the samples compressed at 170 °C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Thermal modification method affects performance properties of the paulownia (Candan et al 2013a) and poplar (Candan et al 2013b) wood materials. Changes in microscopic characteristics because of thermally compressing procedure were examined by Dogu et al (2016) and Dogu et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal modification method affects performance properties of the paulownia (Candan et al 2013a) and poplar (Candan et al 2013b) wood materials. Changes in microscopic characteristics because of thermally compressing procedure were examined by Dogu et al (2016) and Dogu et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, sugarcane bagasse exhibited yields of 18.0 g per 100 g DW (raw) and 36.4 g per 100 g DW (separated cellulose), 72 while hybrid poplar wood yielded 17.7 g per 100 g DW. 73 The high sugar yield from Paulownia wood could be due to its unique large pore size, 74,75 leading to a weaker lignocellulosic structure and hence a higher sugar processability. As demonstrated so far, selective glucose and xylose production from Paulownia wood is possible and is described in depth in ESI Notes 2.…”
Section: Pretreatment Of Paulownia Wood To Sugarmentioning
confidence: 99%
“…In addition, similar changes were obtained in both directions. Dogu et al (2017) similarly applied thermal compression method to paulownia wood with only 20 bar pressure at the same temperatures. They observed that slightly more cellular damage occurred in the treated samples and found that distribution of deformation was not uniform in the growth rings of the treated samples.…”
Section: Rezultati I Raspravamentioning
confidence: 99%